Correlation between Estrogen Metabolites and Antioxidant Defense Systems in Premenopausal and Postmenopausal Women. A Clinical Study - Hanana Hameed, Aaisha Qadir, Tariq Hussain, Arifa Inayat, Nosheen Sikandar Baloch, Azhar Ijaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Estrogens and their metabolites influence systemic oxidative balance by directly scavenging reactive oxygen species and upregulating antioxidant enzymes. Menopause leads to a marked decline in circulating estrogens, potentially diminishing antioxidant defenses. Objective: To evaluate the correlation between specific estrogen metabolites and key antioxidant defense parameters in premenopausal and postmenopausal women. Methodology: In this cross‐sectional study conducted from June 2022 to May 2023 at the Gynecology and Obstetrics Department, Unit 3, Civil Hospital, Quetta, seventy women (thirty‐five premenopausal, thirty‐five postmenopausal) were enrolled. After an overnight fast, venous blood was drawn between 08:00 and 10:00 AM. Plasma concentrations of estradiol (E₂), estrone (E₁), 2-hydroxyestrone (2-OHE₁), and 16α-hydroxyestrone (16α-OHE₁) were quantified by high‐performance liquid chromatography. Activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) were measured via established spectrophotometric assays, and total antioxidant capacity (TAC) was determined using the ferric reducing antioxidant power method. Group comparisons employed independent t-tests, and Pearson’s correlation assessed relationships between estrogen metabolites and antioxidant markers. Results: Premenopausal women demonstrated significantly higher mean E₂ (54.1 ± 14.5 pg/mL vs. 12.5 ± 5.9 pg/mL; p < 0.001), E₁ (45.5 ± 12.1 pg/mL vs. 23.0 ± 9.1 pg/mL; p < 0.001), and 2-OHE₁ (19.0 ± 5.3 pg/mL vs. 9.8 ± 3.9 pg/mL; p = 0.002). There was no significant difference in 16α-OHE₁ (12.0 ± 4.6 pg/mL vs. 10.5 ± 4.0 pg/mL; p = 0.15). SOD activity (8.1 ± 1.8 U/mL vs. 5.7 ± 1.5 U/mL; p < 0.001), CAT activity (49.0 ± 9.0 U/mL vs. 34.5 ± 7.8 U/mL; p < 0.001), GPx activity (12.3 ± 3.2 U/mL vs. 7.8 ± 2.9 U/mL; p < 0.001), and TAC (1245 ± 215 µmol Fe²⁺/L vs. 925 ± 185 µmol Fe²⁺/L; p < 0.001) were all significantly greater in premenopausal women. Estradiol correlated strongly with SOD (r = 0.69; p < 0.001), CAT (r = 0.62; p = 0.001), GPx (r = 0.58; p = 0.003), and TAC (r = 0.56; p = 0.005). The metabolite 2-OHE₁ correlated positively with TAC (r = 0.54; p = 0.004) and SOD (r = 0.50; p = 0.006). In contrast, 16α-OHE₁ was weakly and inversely correlated with GPx (r = −0.32; p = 0.045). Conclusion: Higher levels of estradiol and the antioxidant‐favoring metabolite 2-OHE₁ in premenopausal women are associated with enhanced antioxidant enzyme activities and total antioxidant capacity. After menopause, the decline in these protective estrogens corresponds to reduced antioxidant defenses, potentially increasing susceptibility to oxidative stress–related pathologies. Keywords: estrogen metabolites; antioxidant defense; premenopausal; postmenopausal; superoxide dismutase; catalase; glutathione peroxidase; total antioxidant capacity